2001
DOI: 10.1080/019697201750361283
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Learning: A Computational Model of the Amygdala

Abstract: We describe work in progress with the aim of constructing a computational model of emotional learning and processing inspired by neurophysiological ¢ndings. The main brain areas modeled are the amygdala and the orbitofrontal cortex and the interaction between them. We want to show that (1) there exists enough physiological data to suggest the overall architecture of a computational model, (2) emotion plays a clear role in learning the behavior. We review neurophysiological data and present a computational mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 30 publications
(66 reference statements)
1
48
0
Order By: Relevance
“…The most significant part of learning algorithm is defining the reward function. Reinforced reward signal is a function of other signals considered as an evaluation function ( [12], [15], and [16]). The output of ties in the amygdala and the orbitofrontal tissue, and the final output of the computational model of the brain emotional learning algorithm are calculated by equations 1-3 respectively.…”
Section: Brain Emotional Learning Algorithmmentioning
confidence: 99%
“…The most significant part of learning algorithm is defining the reward function. Reinforced reward signal is a function of other signals considered as an evaluation function ( [12], [15], and [16]). The output of ties in the amygdala and the orbitofrontal tissue, and the final output of the computational model of the brain emotional learning algorithm are calculated by equations 1-3 respectively.…”
Section: Brain Emotional Learning Algorithmmentioning
confidence: 99%
“…The face is seen as an emotional stimulus. Using the cognitive system algebra [11], we showed that a simple sensorymotor architecture based on a classical conditioning paradigm [20,2] can learn to recognize facial expressions online. Furthermore, the dynamics of the humanrobot interaction bring important but non explicit signals, such as the interaction rhythm that helps the system to perform the face/non face discrimination.…”
Section: Modelmentioning
confidence: 99%
“…However, extinction and other related phenomena were not simulated. Balkenius and Morén (2001) proposed a neural network model for emotional conditioning focusing on the amygdala and the orbitofrontal cortex and their interaction. Amygdala was the locus of acquisition and the orbitofrontal cortex was the site for extinction learning.…”
Section: Modeling Fear Memories -A Simple Computational Modelmentioning
confidence: 99%